Stream Clustering for Selection Recommendations Using K-Means Algorithm: A Case Study in the Informatics Study Program - Anggraini, Riska Fahmita; Sau'da, Siti (Journal of Information System and Informatics, 2023)
Concentration Stream for a major is a process where students focus their attention on a specific discipline according to their interests. The purpose of specialization is to better orient students to the knowledge they have gained from previous courses, so that they can have a clearer focus. In the Informatics Engineering study program at Bina Darma University there are 3 concentrations, namely: Software Engineering, Network Engineering, Data Analytics. The absence of a system that helps students choose a major concentration makes it quite difficult for students to know their academic abilities. By looking at these problems, this research aims to build a Recommendation system for selecting Mk-Stream Concentrations using the K-Means grouping approach using the K-Means cluster method. Where student academic achievement data from the first semester to the 4th semester is used as a variable in the calculations.